Določevanje nevtralne točke pri ploskovnem valjanju - León, J. (Strojniški vestnik, 2007)
Studies of rolling processes are very interesting because a large quantity of produced parts are rolled at some point in their fabrication. In this paper the flat rolling process is analyzed using the FEM and an analytical method in order to determine how the reduction, the velocity of the strip and the frictional coefficient affect the position of the neutral point. Both the analytical and FEM results are compared and we can say that analytical equations and the FEM modeling are in good agreement. The plane strain assumption is used in the FEM and in the analytical study, so, in order to study stress and strain, a two-dimensional mesh was considered for all the models. With such models, the deflection of the rolls for different strip thicknesses can be determined. The studied configuration is a four-high rolling system and the rolls and the strip are meshed in order to obtain theirstrain, stress, displacements and velocity fields.
Keywords: valjanje; modeliranje; finite element method; metoda končnih elementov; metoda SLAB